SMOKING, PHYSICAL INACTIVITY AND DIETARY WITH HYPERTENSION IN THE ELDERLY: A SYSTEMATIC REVIEW AND META-ANALYSIS: Merokok, Aktivitas Fisik, dan Pola Diet dengan Hipertensi pada Lansia: Sistematik Review dan Meta Analisis - Nuraisyah, Fatma; Irjayanti, Apriyana; Irmanto, Maxsi; Noorkhalisah, Noorkhalisah (Universitas Airlangga, 2025)
Background: The condition of the elderly can affect blood pressure because they may struggle to balance both psychologically and physiologically. Lifestyle can affect risk factors for hypertension. Purpose: To examine lifestyle risk factors for the incidence of hypertension in the elderly with a systematic review and meta-analysis. Methods: Eight electronic databases, including PubMed, Science PubMed, ScienceDirect, NCBI, ProQuest, and EBSCO Journals Online, were searched for studies published in English from 2017 to December 2023. Quality was assessed using the Joanna Briggs Institute (JBI) for cross-sectional and case-control studies. We further categorized the outcomes into smoking, physical activity, Diet, and hypertension in the elderly. We analyzed them using the Review Manager 5.3 application with both fixed-effect and random-effect models. Results: Eight studies and 30,821 subjects were included, with fair to excellent quality. Based on the meta-analysis, not dieting (AOR = 1.37; 95% CI = 1.17-1.61; p < 0.001) was a statistically significant risk factor for hypertension in the elderly. Conclusion: Not dieting is are risk factor for hypertension in the elderly.